Which one doesn't belong? : playing with shapes - Danielson, Christopher (Charlesbridge, 2019)
"Every page of this innovative picture book contains a thoughtfully designed set of four shapes and the question 'Which one doesn't belong?' Each of the shapes could be a correct answer to the question. Because there is no one right answer, children naturally shift their focus to justifications and arguments based on the shapes' geometric properties."--